Impact of COVID-19 on the endocrine system - D. N. Zadumina; V. V. Skvortsov; D. A. Shtonda (Лечащий Врач)
. Coronavirus infection is a highly contagious disease caused by the SARS-CoV-2 virus. Its targets are any organ systems. Infection begins with the entry of SARS-CoV-2 into target cells. They have type II angiotensin-converting enzyme receptors. SARS-CoV-2 infects target cells with the help of the extracellular domain of ACE-2, as well as the transmembrane protein TMPRSS2. Coronavirus blocks the activity of ACE2, as a natural generator of angiotensin peptides, disrupting the balance of hemovascular control. Under normal conditions, this mission is performed by a complex of ACE/ACE2 enzymes that control the synthesis and physiological activity of angiotensin and kinin peptides in the body. Changes in the ratios of the angiotensin-bradykinin axis and cytokine stress are associated with endothelial dysfunction and multiple vascular disorders. Receptors for angiotensin-converting enzyme-2 are widely expressed in various tissues, including adipose, as well as the pancreas and thyroid glands, pituitary gland, adrenal glands and gonads, which may be the cause of the development of extrapulmonary complications of the new coronavirus infection COVID-19, including complications from side of the endocrine system, especially vulnerable due to the expression of the angiotensin-converting enzyme-2 receptor. COVID 19 primarily affects the respiratory system and also affects other organs and systems, including the endocrine system. Today, it is important to study the effect of COVID-19 on the endocrine part of the pancreas, hypothalamic-pituitary-adrenal and hypothalamic-pituitary-thyroid axis. Of greatest interest are questions about possible long-term consequences associated with the function of the reproductive system. The most severe course of COVID-19 is typical for the elderly with endocrinopathies and other chronic diseases. There is speculation that selective sodium-dependent glucose cotransporter type 2 (SGLT-2) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists, pioglitazone, and even insulin can induce overexpression of ACE-2 receptors, which can have serious negative consequences for people with diabetes in case of infection with SARS-CoV-2. Clinical features of the course of a new coronavirus infection, probable complications, implemented and tested treatment regimens, pleiotropic and undesirable effects of various drugs, the duration of patient rehabilitation – all this is extremely important for patients with endocrine pathology, including autoimmune genesis.